The Challenges and Importance of Teaching Effective Business Writing to EFL Students - Tamari Dolidze (European Scientific Journal, ESJ, 2017)
Writing, in general requires conscious effort and much practice in composing, developing, and analyzing ideas. Students writing in a second language are also faced with social and cognitive challenges related to second language acquisition. The Article explores some of the challenges of in particular business writing in English and once again emphasizes the importance of teaching effective business writing to EFL Students for their better career opportunities and further success.